“Todos juntos contra Aedes aegypti” – O desafio do controle vetorial - SMP, Sampaio; GL, Barbosa; ITRN, Ferreira; M, Pereira; DMV, Wanderley; Junior DP, Fonseca (BEPA. Boletim Epidemiológico Paulista, 2016)